Sustainable production of sorbitol from biomass using green technology approach - Mimi Sakinah, A. M. (Penerbit UMP, 2010)
Sorbitol is a monosaccharides composed of six-carbon sugar alcohol. Sorbitol is produced from glucose by digestion with lactobacillus bacteria during fermentation process. This research use glucose which is produced from one of nature's most abundant raw material cellulose (sawdust) using enzymatic reaction. Sorbitol is a low caloric sugar alcohol that is widely used in a range of food products such as confectionery, chewing gum, candy, desserts, ice cream, and diabetic foods, based on its sweetness and its high solubility. Sorbitol has a relative sweetness of around 60% compared to that of sucrose and displays, a fold higher solubility in water than mannitol. It is non cariogenic and may be useful to people with diabetes. These properties have led to the commercial application of sorbitol in food, pharmaceutical and cosmetic industries as a nutrient, sweetening agent and excipient.